An analysis of Speech Function Used by SEA Today News’ Speakers to Present Indonesian Perspective to the World - Natasha Ayalus Yoan Yola Yolanda; Ouda Teda Ena (Edu-Ling: Journal of English Education and Linguistics, 2022)
Abstract People use language to communicate. While communicating, people have their own ways to deliver their ideas. The language they used is constructed differently based on their own purposes. This research was conducted to study this phenomenon. It aimed at analyzing the speech function used by SEA Today News’ speakers to present the Indonesian perspective to the world. The data were collected from SEA Today News YouTube videos and were analyzed using a qualitative method. The analysis was formulated systematically to answer these two research questions: 1) What speech function categories are found in the Sea Today News video? and 2) What are the purposes of using those speech functions found? The results show that the four speakers in the SEA Today News video used all the speech functions related to their purposes. The most used speech function is ‘statement’ that revealed that the main purpose of the speakers in the SEA Today News video was to 'share information about the topic they discussed, Batik. Furthermore, it was also found that the four speakers in the SEA Today News video respond to each other’s utterances positively with no misunderstanding at all. It indicates the good communication that happens between the speakers.